Introduction: Coloniality, Educational Leadership, and White Supremacy: The Other Global Pandemic. (December 2022) - Marsh, Tyson E.J.; Wright, James; Khalifa, Muhammad; López, Gerardo R.
In lieu of writing a separate introduction to this special issue, the three guest editors invited the EAQ Editor-In-Chief to join them as a coauthor in their introduction. López, agreed but took a few liberties with the draft that was provided to him by the guest editors. The result is an imagined "conversation" that did not actually take place but is highly probable given the deep admiration and mutual respect the four individuals have for each other both as individuals and as scholars. This introductory conversation situates the theme of the special issue within the larger scope of educational leadership while simultaneously troubling the role of school leaders as agents of Coloniality.